From Farms to Tourism : Two Decades of Agritourism Trends – A Bibliometric Analysis - Mude, Girish; Saha, Shantanu (Indian Journal of Marketing, 2025)
Purpose : This study investigated agritourism trends, examining how it diversified rural businesses and contributed to rural economies. It identified the determinants driving agritourism and its various typologies by exploring existing literature. Design/Methodology/Approach : A comprehensive bibliometric analysis was conducted using the biblioshiny tool in RStudio, analyzing 1,104 articles from the Web of Science (WoS) database. The study assessed the most cited papers, key contributing authors, and prominent journals. Additionally, a content analysis was performed to uncover emerging themes and research areas in agritourism. Findings : The results revealed a growing acceptance of agritourism as a rural economic diversification strategy. The study identified leading authors, institutions, and countries contributing to agritourism research and the evolution of major research themes over time. The analysis underscored the economic, social, and environmental benefits of agritourism while also highlighting the associated challenges. Practical Implications : The study provided insights for policymakers, rural developers, and agritourism entrepreneurs in designing effective strategies for sustainable rural development. Understanding agritourism’s motivations and challenges aided in formulating supportive policies and development frameworks. However, the study was limited by its reliance on bibliometric analysis, which may not have fully captured qualitative aspects of agritourism practices. Additionally, the exclusion of non-English publications and reliance on WoS data may have resulted in potential bias and omission of relevant studies from other databases. Originality : This study adopted a novel approach by integrating bibliometric and content analysis to examine agritourism. By identifying key research trends and themes, it enhanced the theoretical understanding of agritourism and its economic impact.